Hsa_circ_0005623 is an indicator for pulmonary artery hypertension associated with congenital heart disease - Zhang, Yuanhao; Han, Yan; Sun, Zirui; Xing, Weizhen; Tang, Hao; Gao, Chuanyu; Han, Yu (Frontiers in Cardiovascular Medicine, 2026)
There is a strong correlation between delayed diagnosis and high mortality rate in pulmonary arterial hypertension (PAH). Recent research indicates that circular RNAs (circRNAs) may serve as potential diagnostic biomarkers for PAH. This study aimed to identify important circRNAs associated with PAH to support early diagnosis and explore possible key disease mechanisms. GSE171827 and GSE113439 were obtained from the Gene Expression Omnibus (GEO) database to evaluate differentially expressed circular RNAs (DECs) and genes (DEGs). MicroRNAs (miRNAs) related to PAH were obtained from the Human microRNA Disease Database (HMDD). We validated changes in DEC expression levels using RT-qPCR in hypoxia- and normoxic-induced human pulmonary artery endothelial cells. Then, the potential relationship between DEC expression levels and mean pulmonary artery pressure (mPAP) in PAH patients was investigated. Finally, bioinformatics analyses were performed to construct a competing endogenous RNA (ceRNA) network and excavate the potential functions of DECs. Only hsa_circ_0005623 expression was significantly downregulated in PAH. Low hsa_circ_0005623 expression levels in the plasma of PAH patients were significantly associated with mPAP (p < 0.001). A ceRNA network comprising 1 circRNA (hsa_circ_0005623), 4 miRNAs (has-miR-424-5p, has-miR-503-5p, has-miR-331-3p, and has-miR-17-3p), and 10 mRNAs (CDH5, ANGPT2, DLL4, CLDN5, ANGPTL4, EDN1, HEY1, GATA2, CLEC14A, and ADM) was identified. Functional enrichment analysis of these 10 hub genes showed enrichment in endothelium development and blood vessel endothelial cell migration. These results suggest that hsa_circ_005623 in plasma is a potential biomarker for early PAH and may play an important role in the development of PAH.